2022
DOI: 10.1136/bmjopen-2021-050211
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution, determinants and trends of full vaccination coverage in children aged 12–59 months in Peru: A subanalysis of the Peruvian Demographic and Health Survey

Abstract: ObjectiveTo assess the spatial distribution, trends and determinants of crude full vaccination coverage (FVC) in children aged 12–59 months between 2010 and 2019 in Peru.Design, setting and analysisA cross-sectional study based on the secondary data analysis of the 2010 and 2019 Peruvian Demographic and Health Surveys (DHSs) was conducted. Logit based multivariate decomposition analysis was employed to identify factors contributing to differences in FVC between 2010 and 2019. The spatial distribution of FVC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Age of household heads who were 41-50 years of age had lower vaccination coverage than those who were 18-30 years old. The nding was supported by a study conducted in Mynamar and Peru [9,10]. It could explain by household head age evidence suggests that either maternal or paternal maturity of age at child growth has been shown to correlate positively with numerous children's health outcomes and development [11].…”
Section: Discussionmentioning
confidence: 86%
“…Age of household heads who were 41-50 years of age had lower vaccination coverage than those who were 18-30 years old. The nding was supported by a study conducted in Mynamar and Peru [9,10]. It could explain by household head age evidence suggests that either maternal or paternal maturity of age at child growth has been shown to correlate positively with numerous children's health outcomes and development [11].…”
Section: Discussionmentioning
confidence: 86%
“…After a high FVC during the 2010-2019 period (albeit stagnant) [22], there was a substantial decline evidenced in 2021 among Peruvian infants. In fact, according to our findings, at least three out of ten Peruvian infants had incomplete vaccination coverage in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide, FVC was 66.19 % among infants aged 12 to 23 months in 2021, which represents a decrease of 7.97 % from 2019 (pre-pandemic era) [22]. Several studies conducted in the post-pandemic era have also revealed a marked decrease in routine vaccination coverage among infants and a slow recovery afterwards [33][34][35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations